Effects of Inflammatory Mediators on Gut Sensititvity - Lionel Bueno; Jean Fioramonti (Canadian Journal of Gastroenterology)
Over the past decade, attention has been paid to the role of visceral sensitivity in the pathophysiology of functional bowel disorders, especially irritable bowel syndrome, and visceral hypersensitivity is the most widely accepted mechanism responsible for both motor alterations and abdominal pain. Inflammatory mediators sensitize primary afferents, especially C-fibre polymodal nociceptors, favouring the recruitment of silent nociceptors that give rise to secondary spinal sensitization. After local tissue injury, the release of chemical mediators such as potassium ions, ATP, bradykinin and prostaglandin E2 directly activate nerve endings and indirectly trigger the release of algesic mediators such as histamine, 5-hydroxytryptamine and nerve growth factor from other cells, which, in turn, stimulate proximal afferent nerve endings and silent nociceptors. Among the intermediary structures activated by inflammatory mediators and susceptible to the release of proalgesic substances, mast cells and platelets play a crucial role; however, immunocytes such as macrophages and neutrophils or sympathetic nerve terminals are also candidates. Moreover, events likely to activate synthesis of mediators by mast cells, such as stress and septic shock, also trigger colonic hypersensitivity. Prolonged visceral hyperalgesia may also depend on spinal sensitization. Anumber of substances are candidates to play a role at the spinal cord level in mediating painful and nonpainful sensations. Among them, substance P, dynorphins and glutamate play a pivotal role in postsynaptic sensitization, particularly during and after gut inflammation. Finally, despite the complexity of the relationship between inflammatory mediators and gut hypersensitivity, numerous results strongly suggest that alteration neuroimmune communications at the gut level may trigger a series of events that give rise to chronic changes in visceral sensitivity.